Case Report: Late-Onset Autosomal Recessive Cerebellar Ataxia Associated With SYNE1 Mutation in a Chinese Family - Qian, Nannan; Wei, Taohua; Yang, Wenming; Wang, Jiuxiang; Zhang, Shijie; Jin, Shan; Dong, Wei; Hao, Wenjie; Yang, Yue; Huang, Ru (Frontiers in Genetics, 2022)
Autosomal recessive cerebellar ataxia type 1 (ARCA-1), also known as autosomal recessive spinocerebellar ataxia type 8 (SCAR8), is caused by spectrin repeat containing nuclear envelope protein 1 (SYNE1) gene mutation. Nesprin-1, encoded by SYNE1, is widely expressed in various tissues, especially in the striated muscle and cerebellum. The destruction of Nesprin-1 is related to neuronal and neuromuscular lesions. It has been reported that SYNE1 gene variation is associated with Emery-Dreifuss muscular dystrophy type 4, arthrogryposis multiplex congenita, SCAR8, and dilated cardiomyopathy. The clinical manifestations of SCAR8 are mainly characterized by relatively pure cerebellar ataxia and may be accompanied by upper and/or lower motor neuron dysfunction. Some affected people may also display cerebellar cognitive affective syndrome. It is conventionally held that the age at the onset of SCAR8 is between 6 and 42 years (the median age is 17 years). Here, we report a pedigree with SCAR8 where the onset age in the proband is 48 years. This case report extends the genetic profile and clinical features of SCAR8. A new pathogenic site (c.7578del; p.S2526Sfs*8) located in SYNE1, which is the genetic cause of the patient, was identified via whole exome sequencing (WES).